2020
DOI: 10.1186/s12866-020-1704-3
|View full text |Cite
|
Sign up to set email alerts
|

The canine oral microbiome: variation in bacterial populations across different niches

Abstract: Background: Microbiota from different niches within the canine oral cavity were profiled and compared. Supragingival plaque and stimulated saliva, were collected alongside samples from the buccal and tongue dorsum mucosa, from 14 Labrador retrievers at three timepoints within a 1 month timeframe. The V3-V4 region of the 16S rRNA gene was sequenced via Illumina MiSeq. Results: Supragingival plaque microbiota had the highest bacterial diversity and the largest number of significant differences in individual taxa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(83 citation statements)
references
References 41 publications
10
72
1
Order By: Relevance
“…In addition, dog saliva and human sweat were artificially spiked to the external tick microbiome to add complex microbial communities of potential hosts. The microbiome of dog saliva and human sweat has been frequently reported and the most abundant bacterial genera of its compositions were not found in tick microbiomes [39,40], which is also true for this study (Supplementary Table S1).…”
Section: Contamination and Decontamination Of Tickssupporting
confidence: 64%
“…In addition, dog saliva and human sweat were artificially spiked to the external tick microbiome to add complex microbial communities of potential hosts. The microbiome of dog saliva and human sweat has been frequently reported and the most abundant bacterial genera of its compositions were not found in tick microbiomes [39,40], which is also true for this study (Supplementary Table S1).…”
Section: Contamination and Decontamination Of Tickssupporting
confidence: 64%
“…Oral microbiome changes have been associated with dental disease, especially periodontal diseases in humans and many animal species, including horses [9,11] dogs [20], cats [21] and cattle [22], but not yet in donkeys suffering from dental abnormalities. Dental floating, the most common dental treatment, plays an important role in dental disease control within farm-raised donkeys.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, oral microbiome samples were obtained from several different niches within the oral cavity. Previous studies have shown that each niche may harbour a unique microbial community, and direct comparisons with such studies are thus limited by the fact that we pooled samples from multiple niches [79].…”
Section: Discussionmentioning
confidence: 99%